The influence of family function and structure on depression in middle aged women - Orji, Eloho J.; Ilesanmi, Stephen O.; Adesokan, Adekunle O.; Akinboboye, Olubankole O.; Ahmed, Adeagbo L.; Akinyugha, Akintunde O.; Edo-Osagie, Ede B.; Atimoh, Charles O.; Kareem, Abiodun J.; Aiyeku, Olajumoke M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Depression is both a mood disorder and a chronic illness of public health importance that accounts for a great socioeconomic burden worldwide. The family influences the health beliefs and health related behavior and it is supposed to provide emotional, financial, physical and emotional support during this period. Aim of the study was to assess the influence of family function and structure on depression in middle-aged women. Methods: The study was a descriptive cross-sectional hospital-based study. Three hundred and two (302) middle-aged women were recruited by simple random sampling method. Relevant data were collected using pretested interviewer administered questionnaire that incorporated family structure, family APGAR and major depression inventory (MDI). Results: More than half (56%) of the participants had a functional family, 66.2% of them were in a monogamous marriage while 64.7% were from a nuclear family. The prevalence of depression was 5.3%; 31.3% of these were from functional family while 68.7% were from dysfunctional family. There was a significant association between family functionality, spousal characteristics such as wife beating and spousal alcohol use with depression. Conclusions: The prevalence of depression was low amongst married middle-aged women currently living with their spouses while no relationship was noted between family structure and depression. Family assessment especially family functionality is highly recommended in assessing depression.